(Genetic Study of Mucopolysaccharidosis in A Sample of Iraqi Children) - Furqan Abdulelah; Mohammed M. Mohammed; Rabab Hassan Baaker (Iraqi Journal of Pharmaceutical Sciences)
Mucopolysaccharidosis (MPS) is a rare heterogenous progressive genetic disorder, which is a subset of lysosomal storage diseases with a consequence of glycosaminoglycans building-up inside the lysosomes which attributed to enzymes absence or deficiency.  This study was aimed to identify mutations that associated with mucopolysaccharidosis of Iraqi children in different Iraqi metabolic centers. While in concerning to the genetic study, the eligible patients who had no genetic analysis and who are not received hematopoietic stem cells transportation were enrolled in this study for molecular confirmation of mucopolysaccharidosis disorders and reporting the existence of any new variants among Iraqi patients. Consequently, the study reports various SNPs are responsible for different MPS types, for instance, there are seven SNPs within IDAU gene of MPS I Iraqi patients, the most frequent one was rs794726877 which accounts for missense c.152G>A. Finally, the study recommends establishment of awareness programs for affected families regarding the genetic conditions, inheritance pattern and potential availability of reproductive options such as In Vitro Fertilization (IVF), educate the population at risk about the risk of genetic disease transmission as a result of inbreed marriage and necessity of availability of prenatal screening and pregnancy termination option in Iraq.